Pulsatile Drug Delivery System: Current Scenario - GANESH RASVE; GANESH BORADE; SIDDHESHWAR DESHMUKH; DR. AMOL TAGALPALLEWAR. (International Journal of Pharma and Bio Sciences, 2011)
The recent research on modified release drug delivery systems gives special attention to pulsatile drug delivery systems because of its unique release pattern. A pulse has to be designed in such a way that a complete and rapid drug release is achieved after the lag time so as to match body’s circadian rhythms with the release of drug which increases the efficacy and safety of drugs by proportioning their peak plasma concentrations during the 24 hours in synchrony with biological rhythm. The aim of this review is to describe several types of drug delivery systems. The data include rational behind the use of chronotherpeutic release of drug and application in various diseases and prerequisites of drug for pulsatile drug delivery system. Advantages, disadvantages and commercial marketed technologies of pulsatile drug delivery system launched by pharmaceutical companies is also included in data.